Ahmad Syafii Maarif’s Journey of Thought: From Fundamentalism to Inclusivism - Muhammad Fuad Fathul Majid; Luqman Al Hakim; Said Hafif Anshori; Ahmad Shofiyullah Fahmi; Galih Prasetio (JUSPI (Jurnal Sejarah Peradaban Islam), 2022)
This article aims to provide a historical narrative about the journey of thinking of one of the leaders of Islamic thought in Indonesia named Ahmad Syafii Maarif. Syafii Maarif experienced a fundamental thought change from a fundamentalist admirer of the Islamic State of Indonesia to becoming an inclusive person who fights for human values. The track record or range of points of intellectual development is divided into three stages. The first turning point or the phase of intellectual formation of Syafii Maarif's thoughts occurred when he received an education at the Muhammadiyah Mu'allimin Madrasah at Balai Tangah, Lintau, West Sumatra. The second point, or phase of intellectual growth, occurred after continuing his studies at Madrasah Mu'allimin Yogyakarta and finished in 1956. The third point, or phase of intellectual development, happened when he attended a doctoral program at the University of Chicago, United States, completed in 1983. At the university, he experienced a significant intellectual turning point by experiencing a new spiritual and intellectual awakening under Fazlur Rahman (1919-1988). This article uses the historical theory of Kuntowijoyo's thoughts, as a form of thought study methodology in which it examines the text, context, and the relationship between the text and society. This article uses a biographical approach to analyze the genealogy of thought and environmental conditions of Ahmad Syafii Maarif.